Electric currents : it's energetic - Linde, Barbara M. (Spotlight on physical science., 2020)
Examines the history and evolution of how electric currents are studied and manipulated and why continued study is important. Includes illustrations and photographs, sidebars, a glossary, a primary source list, sources for further information, and an index.